2021
DOI: 10.1016/j.celrep.2021.109444
|View full text |Cite
|
Sign up to set email alerts
|

Behavior determines the hippocampal spatial mapping of a multisensory environment

Abstract: Highlights d Mice navigate the same multisensory environment using vision, odor, or both d Hippocampal spatial mapping depends on the modality used for navigation d Switching between visual and olfactory navigation causes global remapping d Navigation of varying modality engages modality-invariant spatial mapping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 78 publications
(100 reference statements)
2
39
0
Order By: Relevance
“…It is possible that, rather than encoding non-spatial “what” information ( O’Keefe and Krupic, 2021 ), “cue cells” in our study could actually be place cells encoding “where” information within a different reference frame ( van Dijk and Fenton, 2018 ; Radvansky et al, 2021 ). However, we observed robust responses in the same cue cells even to an odor cue administered randomly in each lap ( Figures 4A – 4C ).…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that, rather than encoding non-spatial “what” information ( O’Keefe and Krupic, 2021 ), “cue cells” in our study could actually be place cells encoding “where” information within a different reference frame ( van Dijk and Fenton, 2018 ; Radvansky et al, 2021 ). However, we observed robust responses in the same cue cells even to an odor cue administered randomly in each lap ( Figures 4A – 4C ).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, our observation of concurrent cue-specific and cue-independent spatial representations could not have been confounded by factors like task requirement or reward setup. Moreover, our findings suggest that previous studies reporting cue-independent spatial representations might have missed parallel cue-specific representations reflected in a different form of neural activity 13, 14, 16 . For this reason, the current study highlights the importance of investigating complementary neural phenomena to obtain a more complete understanding of the neural representations underlying cognitive maps.…”
Section: Discussionmentioning
confidence: 59%
“…When the sensory inputs for encoding the same physical space changed, previous studies have observed either cue-specific spatial representations in the hippocampus 9 , or cue-independent spatial representations in RSC 14 and in the brain-wide functional connectivity pattern 16 . A recent study found that whether altering spatial inputs invoked cue-specific or cue-independent spatial representations in the hippocampus depended on whether different cue types were congruent in defining the reward location 13 . Taken together, previous studies have observed either cue-specific or cue-independent spatial representations but not both at the same time in the same spatial context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical comparisons for CPFE studies were performed using one-way ANOVA followed by Dunnett’s multiple comparisons tests, and dose dependence was assessed by fitting data to a logistic equation (GraphPad Prism v9.3.1). Comparisons for calcium imaging data were made by fitting linear mixed effects models, with statistical significance derived from Kenward-Roger type III & likelihood ratio tests (Bates et al, 2015) using RStudio, 2021.09.0 Build 351 (R Core Team (2021). R: A language and environment for statistical computing.…”
Section: Methodsmentioning
confidence: 99%